Habitat and movement selection processes of American lobster/jakej within a restricted bay in the Bras d’Or Lake/Pitu’paq, Nova Scotia, Canada - Shannon Landovskis; Megan Bailey; Sara Iverson; Skyler Jeddore; Robert J. Lennox; Caelin Murray; Fred Whoriskey (Movement Ecology, 2024)
Abstract American lobster inhabit the unique, brackish Bras d’Or Lake system, although densities are low compared to areas with similar habitats in the Atlantic Ocean. Nevertheless, lobsters are an important part of local First Nation (Mi’kmaq) food and culture. We used acoustic telemetry and habitat mapping, combined with local Mi’kmaw knowledge, to document the movements and habitat use of adult lobsters within a section of the Lake. Movement patterns of acoustically tagged individual lobsters were analyzed with both resource selection functions and integrated step selection functions using data obtained from a high-resolution VEMCO Positioning System within a restricted bay in the Bras d’Or Lake. The resource selection function suggested stronger selections of substrates that contained a combination of soft and hard sediments. While the integrated step selection functions found substantial individual variability in habitat selections, there was a trend for lobsters to exhibit more resident behaviour on the combined soft/hard substrates despite the fact these sediments provided little in the way of obvious shelters for the animals. Adult lobsters at this site have very little risk of predation, which presumably allows them to freely exhibit exploratory behaviours and reduce their association with substrates that provide shelters.